Cryopyrin-Associated Periodic Syndromes (CAPS): Pathogenesis, Clinical Manifestations, and IL-1-Targeted Therapeutic Strategies - Joanna Nadaj; Bartosz Czyżewski; Anna Mariankowska; Anna Dróżdż; Weronika Posuniak; Michał Dorota; Karol Kozłowski; Oliwia Kawa; Wojciech Żywiec; Cezary Milczarek (Journal of Education, Health and Sport, 2025)
Cryopyrin-associated periodic syndromes (CAPS) are a group of rare, genetically determined autoinflammatory diseases resulting from gain-of-function mutations in the NLRP3 gene. These mutations lead to constitutive activation of the inflammasome and overproduction of interleukin-1β and interleukin-18, driving chronic systemic inflammation. CAPS encompasses three distinct clinical phenotypes—familial cold autoinflammatory syndrome (FCAS), Muckle-Wells syndrome (MWS), and chronic infantile neurologic cutaneous and articular syndrome (CINCA/NOMID)—which vary in severity and organ involvement. FCAS presents the mildest course with cold-induced symptoms, while CINCA/NOMID is the most severe form, often associated with CNS involvement and progressive sensorineural deficits.